Patient and physician perception of natural orifice transluminal endoscopic appendectomy - Hucl, Tomas (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate perception of natural orifice transluminal endoscopic surgery (NOTES) as a potential technique for appendectomy. METHODS: One hundred patients undergoing endoscopy and 100 physicians were given a questionnaire describing in detail the techniques of NOTES and laparoscopic appendectomy. They were asked about the reasons for their preference, choice of orifice, and extent of complication risk they were willing to accept. RESULTS: Fifty patients (50%) and only 21 physicians (21%) preferred NOTES (P < 0.001). Patients had previously heard of NOTES less frequently (7% vs 73%, P < 0.001) and had undergone endoscopy more frequently (88% vs 36%, P < 0.001) than physicians. Absence of hernia was the most common reason for NOTES preference in physicians (80% vs 44%, P = 0.003), whereas reduced pain was the most common reason in patients (66% vs 52%). Physicians were more likely to refuse NOTES as a novel and unsure technique (P < 0.001) and having an increased risk of infection (P < 0.001). The preferred access site in both groups was colon followed by stomach, with vagina being rarely preferred. In multivariable modeling, those with high-school education [odds ratio (OR): 2.68, 95% confidence interval (CI): 1.23-5.83] and prior colonoscopy (OR: 2.10, 95% CI: 1.05-4.19) were more likely to prefer NOTES over laparoscopic appendectomy. There was a steep decline in NOTES preference with increased rate of procedural complications. Male patients were more likely to consent to their wives vaginal NOTES appendectomy than male physicians (P = 0.02). CONCLUSION: The preference of NOTES for appendectomy was greater in patients than physicians and was related to reduced pain and absence of hernia rather than lack of scarring.